2020
DOI: 10.3390/coatings10121204
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Influence of Microdroplets on the Coatings Nanolayer Structure

Abstract: The paper presents the results of studies focused on the specific features typical for the formation of the shape and structure of microdroplets embedded into the structure of the Ti–TiN–(Ti,Cr,Mo,Al)N and Ti–TiN–(Ti,Al,Nb,Zr)N coatings during their deposition. Three main microdroplet shapes—a sphere, a tear, and a lens—have been considered. The specific features typical for the formation of secondary layered structures on the surface of some microdroplets have also been examined. As a result of the conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…These surface characteristics significantly influence the mechanical and tribological properties of the surface, as they act as stress concentrators, impacting crack behavior. Cracks can initiate or propagate around sub-micron-sized defects and can be associated with droplets of micrometric sizes [ 22 , 36 , 37 , 38 , 39 ]. The cross-sections of the coatings, illustrated in Figure 2 d–f, display a dense columnar growth pattern typical of ceramic coatings such as TiN.…”
Section: Resultsmentioning
confidence: 99%
“…These surface characteristics significantly influence the mechanical and tribological properties of the surface, as they act as stress concentrators, impacting crack behavior. Cracks can initiate or propagate around sub-micron-sized defects and can be associated with droplets of micrometric sizes [ 22 , 36 , 37 , 38 , 39 ]. The cross-sections of the coatings, illustrated in Figure 2 d–f, display a dense columnar growth pattern typical of ceramic coatings such as TiN.…”
Section: Resultsmentioning
confidence: 99%
“…In many machine elements such as gear wheel surface, bolts, trunnions, shafts, pin bearings, the desired wear and crushing resistance is achieved by hardening only the surface layer, the thickness of which is mostly 0.1-2 mm, while the inner parts remain tough. [1][2][3][4] Surface hardening is one of the main ways to increase the wear resistance of parts and frictional units. In industry, there are more than a hundred methods of surface hardening, but not all have found industrial application.…”
Section: Introductionmentioning
confidence: 99%
“…Disposition of the microdroplets is technically difficult and the equipment is costly. Fortunately, it was found that the average size and number of microdroplets increased with increasing the cathode arc current, gas pressure, and cathode target temperature [8], which is still acceptable in practice if the size is not too large.…”
Section: Introductionmentioning
confidence: 99%